THE USE OF COLLABORATIVE TECHNIQUE IN IMPROVING STUDENTS’ ABILITY IN WRITING A DESCRIPTIVE TEXT - Irvan Farizi; Fitri Fauzyah; Yanuarti Apsari (IKIP Siliwangi, 2019)
This study aims to determine the method of Think Pair Share (TPS) learning methods in improving writing skills in students, the research instruments used test questions. This study uses Action Research Design in 2 classes with the aim of improving the quality or problem solving in 2 groups carefully and observing the success rate of the action. The results of the study showed that the application of the Think Pair Share Learning (TPS) Method could improve students' writing skills, especially descriptive text. Before the implementation of the action, the score obtained was 43%, then in the first cycle it increased to 76%, so using the think pair share method improved the writing ability of students, especially descriptive text.